The Comparison of Work Productivity Between Nurses with Insight of Occupational Health Nursing (OHN) and of Those Without It - Tukayo, Isak Jurun Hans; Hardy, Syaifoel (University of Muhammadiyah Malang, 2020)
ABSTRACTÂ Introduction: Occupational Health Nursing (OHN) is very important to be studied by nursing students considering the industial demands are very high on the importance of the health of workers in the future. The problem is they don't get proportional insights to OHN. This needs evidence of its effect on nursesâ€™ work productivity. Objective: The objective is to compare the level of work productivity between nurses who have the OHN insight with those without it, working in the industrial setting. Method: The method is Comparative Study with Cross Sectional Study Design with nursing students, nurses and Indonesian nurses working abroad as the populations. The sampling technique is non-probability sampling with a total sample of 130 respondents. The data collection tool uses a questionnaire and Likert Scale, compiled based on the Health Belief Model Theory (HBM). The data were analyzed by the Paired Sample T-test to see the differences between nurses who had received OHN subject and those who had never. Result: The results show significant differences on level of understanding between nurses who have received subject material about OHN with those who have never had it, with a p-value of 0,000. Discussion: Significant productivity differences between nurses who have received lecture material about OHN and those who did not, which can be used as criticism or input for nursing education in Indonesia.